Gender differences in occupational exposure patterns. Issue 12 (12th April 2011) - Eng, Amanda; 't Mannetje, Andrea; McLean, Dave; Ellison-Loschmann, Lis; Cheng, Soo; Pearce, Neil
Abstract : Objectives: The authors conducted a population-based survey to examine gender differences in occupational exposure patterns and to investigate whether any observed differences are due to: (a) gender differences in occupational distribution; and/or (b) gender differences in tasks within occupations. Methods: Men and women aged 20–64 years were randomly selected from the Electoral Roll and invited to take part in a telephone interview, which collected information on self-reported occupational exposure to specific dusts and chemicals, physical exposures and organisational factors. The authors used logistic regression to calculate prevalence ORs and 95% CIs comparing the exposure prevalence of males (n=1431) and females (n=1572), adjusting for age. To investigate whether men and women in the same occupation were equally exposed, the authors also matched males to females on current occupation using the five-digit code (n=1208) and conducted conditional logistic regression adjusting for age. Results: Overall, male workers were two to four times more likely to report exposure to dust and chemical substances, loud noise, irregular hours, night shifts and vibrating tools. Women were 30% more likely to report repetitive tasks and working at high speed, and more likely to report exposure to disinfectants, hair dyes and textile dust. When men were compared with women with the same occupation, gender differences were attenuated. However, males remained significantly more likely to report exposure to welding fumes, herbicides, wood dust, solvents, tools that vibrate, irregular hours and night-shift work. Women remained more likely to report repetitive tasks and working at high speed, and in addition were more likely to report awkward or tiring positions compared with men with the same occupation. Conclusion: This population-based study showed substantial differences in occupational exposure patterns between men and women, even within the same occupation. Thus, the influence of gender should not be overlooked in occupational health research.